Cation-Controlled Excimer Packing in Langmuir-Blodgett Films of Hemicyanine Amphiphilic Chromoionophores - Selektor, S L (Langmuir : the ACS journal of surfaces and colloids, 2016)
Supramolecular structure of ultrathin films of hemicyanine dye bearing a crown ether group (CrHCR) was tuned by lateral pressure and investigated by means of compression isotherms, UV-vis and fluorescence spectroscopies, and X-ray reflectivity. Two different types of aggregation were revealed, depending on the absence or the presence of metal cations in the water subphase. While CrHCR forms at high surface pressures head-to-tail stacking aggregates on pure water, changing the subphase to a metal-cation-containing one leads to the appearance of well-defined excimers with head-to-head orientation. The structure of monolayers transferred onto solid supports by the Langmuir-Blodgett (LB) technique was examined by use of X-ray reflectivity measurements and molecular modeling. A model of cation-induced excimer formation in hemicyanine Langmuir monolayers is proposed. Finally, fluorescence emission properties of LB films of CrHCR can be managed by appropriate changes in the subphase composition, this last one determining the type of chromophore aggregation